Challenges of the Implementation of the Olympic Values Education in Indonesia: A Case of Asean University Games 2024 - Mutohir, Toho Cholik; Prasetya, Muhammad Reza Azis; Firmansyah, Awang; Ardha, Muchamad Arif Al; Ayubi, Novadri; Sriundy, I Made; Muhyi, Muhammad (ASEAN Journal of Sport for Development and Peace, 2025)
This research investigates the understanding and challenges of implementing Olympic Values—Excellence, Friendship, and Respect—in Indonesia's sports education. While the International Olympic Committee (IOC) promotes these values to foster ethical behavior among athletes, their integration into Indonesian universities faces significant obstacles due to limited awareness and institutional support. Utilizing a quantitative descriptive approach, data were collected from 178 respondents, including students and lecturers, who had not participated in the ASEAN University Games (AUG). Results indicated that 67% of respondents demonstrated a good understanding of Olympic Values, with 41% emphasizing their importance in daily life and sports. Social media (45%) was identified as the primary source of information. However, challenges persist, such as a lack of awareness (28.1%), insufficient curriculum integration (16.9%), and inadequate resources (14%). The study concludes that while awareness of Olympic Values exists, significant efforts are required to enhance their practical application. Recommendations include increasing institutional support, revising curricula, and improving resource allocation to better incorporate Olympic Values in Indonesian sports education.